2020
DOI: 10.3390/jof6040371
|View full text |Cite
|
Sign up to set email alerts
|

Diversity within Aspergillus niger Clade and Description of a New Species: Aspergillus vinaceus sp. nov.

Abstract: Diversity of species within Aspergillus niger clade, currently represented by A. niger sensu stricto and A. welwitshiae, was investigated combining three-locus gene sequences, Random Amplified Polymorphic DNA, secondary metabolites profile and morphology. Firstly, approximately 700 accessions belonging to this clade were investigated using calmodulin gene sequences. Based on these sequences, eight haplotypes were clearly identified as A. niger (n = 247) and 17 as A. welwitschiae (n = 403). However, calmodulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…Our phylogenetic analyses of a combined five genes (cam, benA, rpb2, tef1, and act) revealed that three new species, A. chiangmaiensis, A. pseudopiperis, and A. pseudotubingensis, formed distinct lineages within the Aspergillus section Nigri. Morphologically, A. chiangmaiensis, A. pseudopiperis, and A. pseudotubingensis have been distinguished from the currently accepted species of Aspergillus section Nigri (Samson et al, 2014;Fungaro et al, 2017;Crous et al, 2018;da Silva et al, 2020;Doilom et al, 2020). The different morphological characteristics identified between the three new species have indicated that only A. chiangmaiensis and A. pseudopiperis could produce sclerotia (Supplementary Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…Our phylogenetic analyses of a combined five genes (cam, benA, rpb2, tef1, and act) revealed that three new species, A. chiangmaiensis, A. pseudopiperis, and A. pseudotubingensis, formed distinct lineages within the Aspergillus section Nigri. Morphologically, A. chiangmaiensis, A. pseudopiperis, and A. pseudotubingensis have been distinguished from the currently accepted species of Aspergillus section Nigri (Samson et al, 2014;Fungaro et al, 2017;Crous et al, 2018;da Silva et al, 2020;Doilom et al, 2020). The different morphological characteristics identified between the three new species have indicated that only A. chiangmaiensis and A. pseudopiperis could produce sclerotia (Supplementary Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…nov. recently described. 33 We mainly identified three cryptic species (A. niger, A. tubingensis, and A. welwitschiae) among the black aspergilli isolates studied. The main observation was that cryptic species were not distributed evenly between EEC and respiratory specimens.…”
Section: Discussionmentioning
confidence: 99%
“…The name A. niger has been used in a broad sense throughout literature to refer to species belonging to Aspergillus section Nigri , the “ A. niger aggregate,” the “black aspergilli,” “the A. niger clade,” or the “ Aspergillus niger group” ( Abarca et al 2004 ; Ferracin et al 2009 ; Nielsen et al 2009 ; da Silva et al 2020 ). However, A. niger is also referred to as a species within Aspergillus section Nigri.…”
Section: Introductionmentioning
confidence: 99%